Suppression of bacterial wilt in susceptible scion of tomato(Solanum lycopersicum ) and brinjal (Solanum melongena ) using Solanum. torvum as resistant rootstock (Current Horticulture, 2024)
Tomato (Lycopersicon esculentum L.) and brinjal (solanum melongena L) is very popular vegetable in India and rich source  of antioxidants, minerals and vitamins (Tomar and Saha, 2018). They suffer from several biotic and abiotic stresses. Among  these, bacterial wilt caused by Ralstonia solanacearum is most devastating and economically important diseases of both. The  several efforts has been taken to overcome these stress. However, grafting was utilized to manage bacterial wilt in tomato  crops worldwide (Ganiyu et al., 2018). The use of tolerant rootstocks for grafting brinjalt varieties is most effective approach  to control bacterial wilt disease (King et al., 2008). Resistance to R. solanacearum has been identified in various accessions of  cultivated brinjal and in distant wild relatives, such as S. capsicoides, S. sisymbriifolium, S. virginianum, S. grandiflorum, S. hispidum,  S. sessiliflorum, S. stramonifolium, S. torvum, S. americanum ,S. nigrum, and S. scabrum (Rotino et al., 2014). There are some reports  of improving production and productivity in horticultural crops using grafting approach such as guava (Psidium guajava) and  pomegranate (Punica granatum) (Nowrozy.,. 2017; Kholia et al., 2022). However, there is no report on in vitro micrografting of  tomato, brinjal, chilli, and citrus. Therefore, cost -effective in vitro micrgrafting protocol of tomato, brinjal, chili, and citrus is  the need of the day. Micrografted tomato and brinjal against Ralstonia solanacearum using bacterial wilt resistance wild brinjal  rootstock, was also evaluated.
Keywords: Bacterial wilt; Brinjal; Micrografting; Rootstock; S. torvum